Medical Students' Attitudes and Awareness toward Teaching and Participation in Formal Clinical Teaching in Iraq - Alsaffar, Hussain; Abdullah, Wasnaa Hadi; Akram, Nabeeha Najatee; Nadhim, Haider; Salman, Mayameen H.; Laylani, Amal Adnan; Yahya, Farah Sameer; Rahim, Ali Ibrahim; Salih, Aso; Jassim, Duralhassan; Salman, Houreleen H.; Ibrahim, Hind Mutar; Gargary, Khalaf; Ibrahim, Ahmad Khalil; Alsayegh, Adyan; Ibrahim, Maysaa Nihad; Al-Dabagh, Jaafar D.; Habeeb, Sawsan Issa (Ibnosina Journal of Medicine and Biomedical Sciences, 2023)
Objective Clinical teaching is essential for the continuity of education of health care professionals. Developing teaching skills is highly required to communicate efficiently and transfer experience and knowledge to others. To our knowledge, medical students across Iraq did not give their perception of clinical teaching in a comprehensive way. Therefore, the aim of this study is to understand our students' perception of clinical teaching and to learn from their responses what subtypes of clinical teaching they may desire the most.Materials and Methods An online survey was distributed among medical students in Iraqi universities between February and April 2022.Results In all, 2,562 students (1,567 females and 995 males) responded from 24 of 26 colleges of medicine in Iraq. The majority of responders were senior students. In total, 73.3% of our students had no previous experience in teaching. Those willing to work in a teaching or academic hospital comprised 84.2% of the students, and 1,563 students were interested in pursuing “clinical teaching” for medical students/residents upon completion of residency. Collective confidence in teaching abilities was rated as 3.4 out of 5. In total, 1,505 medical students felt they would be interested to have an elective period in medical education, and the majority voted for a 1-month period. Male students perceived more confidence in their variable teaching abilities compared to females (p < 0.05).Conclusion This is the first study among Iraqi medical students that revealed a desire to avail of a 4-week elective in clinical teaching and become incorporated within the undergraduate curriculum of medical schools in Iraq.
Keywords: clinical teaching; education; medical students; awareness; Iraq